Penerapan Islamic Social Reporting (ISR) Di PT. BPRS Amanah Bangsa Kc. Kisaran - Sapitra Andani; Isra Hayati (Yayasan Rahmat Islamiyah, 2022)
This study aims to determine the transparency in the application of Islamic Social Reporting (ISR) at PT. BPRS Amanah Bangsa Kc. range. The research approach used in this study uses a qualitative approach. Respondents in this study 5 people consisting of company directors and employees. Data collection techniques using interviews. The method used in this research is qualitative method. The results show that the company composes and discloses the Islamic Social Reporting (ISR) every year in accordance with the Islamic Social Reporting index at the Amanah Bangsa BPRS is indeed very good in accordance with the regulations of the Financial Services Authority. Almost all items used as references in this study were disclosed by BPRS Amanah Bangsa Kc Kisaran. BPRS Amanah Bangsa Kc Kisaran revealed 6 themes including: Funding and Investment, Products and Services, Employees, Society, Environment, Corporate Governance.